The impact of macroeconomic variables on investment strategies and corporate growth in developing economies - Rinda Fithriyana; Henrycus Winarto Santoso; Gregorius Paulus Tahu; Loso Judijanto; Dita Rosyalita (Indonesian Institute For Counseling, Education and Therapy, 2026)
This study examines the impact of macroeconomic variables on investment strategies and corporate growth in developing economies through a library research approach. The research focuses on the influence of key macroeconomic indicators, including inflation rates, interest rates, exchange rates, and economic growth, on corporate investment decision-making and firm performance. Data were collected from relevant books, academic journals, research reports, and scientific publications and analyzed using content analysis techniques. The findings reveal that macroeconomic conditions significantly affect firms’ investment behavior by influencing capital costs, expected returns, and business uncertainty. Economic growth and macroeconomic stability encourage investment activities and support corporate expansion, while high inflation, rising interest rates, and exchange rate volatility tend to hinder investment and reduce growth opportunities. The study also finds that firms often adjust or postpone investment decisions during periods of economic uncertainty. Overall, the research highlights the importance of stable macroeconomic environments and adaptive investment strategies in promoting sustainable corporate growth and long-term economic development in developing economies.